Evaluation of ethanol production by a new isolate of yeast during fermentation in synthetic medium and sugarcane bagasse hemicellulosic hydrolysate - Hande, Aparna; Mahajan, Siddharth A.; Prabhune, Asmita (Annals of Microbiology, 2013)
A new xylose fermenting yeast was isolated from over-ripe banana by enrichment in xylose-containing medium. The phylogenetic analysis of ITS1-5.8S-ITS2 region sequences of ribosomal RNA of isolate BY2 revealed that it shows affiliation to genus Pichia and clades with Pichia caribbica. In batch fermentation, Pichia strain BY2 fermented xylose, producing 15 g l(-1) ethanol from 30 g l(-1) xylose under shaking conditions at 28A degrees C, with ethanol yield of 0.5 g g(-1) and volumetric productivity of 0.31 g l(-1) h(-1). The optimum pH range for ethanol production from xylose by Pichia strain BY2 was 5-7. Pichia strain BY2 also produced 6.08 g l(-1) ethanol from 30 g l(-1) arabinose. Pichia strain BY2 can utilize sugarcane bagasse hemicellulose acid hydrolysate for alcohol production, efficiency of fermentation was improved by neutralization, and sequential use of activated charcoal adsorption method. Percent total sugar utilized and ethanol yield for the untreated hydrolysate was 17.14% w/v and 0.33 g g(-1), respectively, compared with 66.79% w/v and 0.45 g g(-1), respectively, for treated hemicellulose acid hydrolysate. This new yeast isolate showed ethanol yield of 0.45 g g(-1) and volumetric productivity of 0.33 g l(-1) h(-1) from sugarcane bagasse hemicellulose hydrolysate detoxified by neutralization and activated charcoal treatment, and has potential application in practical process of ethanol production from lignocellulosic hydrolysate.
Keywords: D-xylose; Ethanol; Pichia; Sugarcane bagasse hemicellulose